Tindak Pidana Tertentu Erotika (Pornografi) - Nadhira, Maula Silmi; Nazwa, Amelia Muthia (Media Hukum Indonesia (MHI), 2025)
Pornography in Indonesia is a legal issue closely related to moral norms and the development of information technology. Etymologically, the term pornography originates from the Greek words pornos (obscene) and graphos (writing), which now encompass various visual, audio, and digital forms containing erotic or indecent elements. In the legal context, the regulation of pornography is governed by Law Number 44 of 2008 concerning Pornography, which specifically distinguishes between pornography and pornoaction. Nevertheless, provisions in the Indonesian Criminal Code (KUHP) remain in effect, particularly those related to morality, such as Articles 281, 282, 283, 532, and 533. With technological advancement, the definition of pornography has expanded to include various media forms such as images, sounds, videos, animations, and digital content. The law also outlines the elements of pornographic criminal acts, which consist of two main components: the act element and the object element. The act element includes producing, distributing, renting, or downloading pornographic materials, while the object element covers content that explicitly displays sexual activity, sexual violence, nudity, or child pornography. Violations of these provisions may result in imprisonment of up to twelve years and fines of up to six billion rupiahs. Therefore, the regulation of pornography in Indonesia serves not only as a legal instrument but also as an effort to preserve morality and decency amid globalization and the rapid advancement of digital technology.